2009
DOI: 10.4049/jimmunol.0713169
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CCR6 Function Reduces the Severity of Experimental Autoimmune Encephalomyelitis via Effects on the Priming Phase of the Immune Response

Abstract: Chemokines are essential for homeostasis and activation of the immune system. The chemokine ligand/receptor pairing CCL20/CCR6 is interesting because these molecules display characteristics of both homeostatic and activation functions. These dual characteristics suggest a role for CCR6 in the priming and effector phases of the immune response. However, while CCR6 has been implicated in the effector phase in several models, a role in the priming phase is less clear. Herein we analyze the role of CCR6 in these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(126 citation statements)
references
References 44 publications
4
120
1
1
Order By: Relevance
“…Previous studies indicated that CCR6/CCL20 interaction was crucial for the development of EAE, since CCR6 -/-mice were resistant to EAE (15) and anti-CCR6 polyclonal antibody treatment prevented the progression of disease (23). Murine EAE was induced by injection of recombinant mouse myelin oligodendrocyte glycoprotein (rmMOG), a model in which antigen-specific B cells contribute to disease pathogenesis (24).…”
Section: Anti-ccr6 Treatment Prevents and Inhibits Clinical Progressimentioning
confidence: 99%
“…Previous studies indicated that CCR6/CCL20 interaction was crucial for the development of EAE, since CCR6 -/-mice were resistant to EAE (15) and anti-CCR6 polyclonal antibody treatment prevented the progression of disease (23). Murine EAE was induced by injection of recombinant mouse myelin oligodendrocyte glycoprotein (rmMOG), a model in which antigen-specific B cells contribute to disease pathogenesis (24).…”
Section: Anti-ccr6 Treatment Prevents and Inhibits Clinical Progressimentioning
confidence: 99%
“…Further investigation of the role of CCR6 expressing cells in a cigarette smoke-induced lung injury model was reported by Bracke et al (2006), who showed reduced numbers of DCs, activated CD8 1 T cells, and neutrophils in Ccr6-deficient mice leading to decreased emphysema in this model of chronic obstructive pulmonary disease (COPD). Liston et al (2009) examined the role of CCR6-expressing cells in both the induction and effector phase of the EAE model of demyelination and central nervous system (CNS) inflammation. Ccr6 2/2 mice had reduced disease scores compared with wild-type mice following immunization with myelin oligodendrocyte glycoprotein (MOG) peptides (Liston et al, 2009 Genome-wide association studies (GWAS) have identified single nucleotide polymorphisms near the CCR6 gene on chromosome 6q27 as novel risk loci for autoimmune Graves' disease, generalized vitiligo, and RA (Chu et al, 2011;Jin et al, 2010a;Quan et al, 2010;Stahl et al, 2010).…”
Section: Maturation Of Dcs Derived From Cd34mentioning
confidence: 99%
“…Liston et al (2009) examined the role of CCR6-expressing cells in both the induction and effector phase of the EAE model of demyelination and central nervous system (CNS) inflammation. Ccr6 2/2 mice had reduced disease scores compared with wild-type mice following immunization with myelin oligodendrocyte glycoprotein (MOG) peptides (Liston et al, 2009 Genome-wide association studies (GWAS) have identified single nucleotide polymorphisms near the CCR6 gene on chromosome 6q27 as novel risk loci for autoimmune Graves' disease, generalized vitiligo, and RA (Chu et al, 2011;Jin et al, 2010a;Quan et al, 2010;Stahl et al, 2010). Of note Kochi et al (2010) identified a dinucleotide polymorphism in the CCR6 gene that was associated with RA susceptibility in two independent cohort studies and was correlated with the level of CCR6 expression and the presence of IL-17 in patient sera.…”
Section: Maturation Of Dcs Derived From Cd34mentioning
confidence: 99%
“…Whereas the initial site-specific entry of Th17 cells via the choroids plexus into the uninflamed CNS was CCR6 dependent, leukocyte infiltration was CCR6 independent at later stages of disease. 30 Furthermore, Liston et al 31 demonstrated that CCR6 drives the priming phase of EAE by mediating the influx of dendritic cells into and the egress of activated lymphocytes from the draining lymph nodes of the CNS. Both of these proposed mechanism for CCR6 function, however, are less important in renal disease.…”
Section: Cd4mentioning
confidence: 99%